2005
DOI: 10.1007/s00442-004-1788-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire on properties of forest soils: a review

Abstract: Many physical, chemical, mineralogical, and biological soil properties can be affected by forest fires. The effects are chiefly a result of burn severity, which consists of peak temperatures and duration of the fire. Climate, vegetation, and topography of the burnt area control the resilience of the soil system; some fire-induced changes can even be permanent. Low to moderate severity fires, such as most of those prescribed in forest management, promote renovation of the dominant vegetation through elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

101
1,949
19
78

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,336 publications
(2,147 citation statements)
references
References 107 publications
101
1,949
19
78
Order By: Relevance
“…It has been predicted the frequency and intensity of wildfire would increase under global warming (Bradstock, 2002;Cary, 2002;Westerling et al, 2006). Fire influences the population and species diversity of the aboveground plants (Bond and Van Wilgen, 1996) and belowground soil properties (Certini, 2005) as well as microorganisms (Vázquez et al, 1993). Niboyet et al (2011) found that fires increased soil nitrous oxide emission when interacting with other factors, such as elevated CO 2 , precipitation and N deposition.…”
Section: Introductionmentioning
confidence: 99%
“…It has been predicted the frequency and intensity of wildfire would increase under global warming (Bradstock, 2002;Cary, 2002;Westerling et al, 2006). Fire influences the population and species diversity of the aboveground plants (Bond and Van Wilgen, 1996) and belowground soil properties (Certini, 2005) as well as microorganisms (Vázquez et al, 1993). Niboyet et al (2011) found that fires increased soil nitrous oxide emission when interacting with other factors, such as elevated CO 2 , precipitation and N deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The mineral soil color is commonly classified as black (semi-combusted organic material), gray or white (ash from organic material), and orange (change in physical structure and lack of organic material) [7,43,48]. Post-fire soil color depends on the amount and type of pre-fire vegetation and surface organic material, their respective moisture contents, and weather (e.g., wind speed, relative humidity, air temperature) during a fire.…”
Section: Resultsmentioning
confidence: 99%
“…Common soil physical properties influenced by fire include water repellency, structure stability, texture, color, post-fire surface temperatures, and abundance of surface organic material [48] (Table 3). Typically erosion only occurs when organic cover is less than 40-50% after a fire [50][51][52]54].…”
Section: Relating the Pfi To Post-fire Physical Soil Responsementioning
confidence: 99%
See 1 more Smart Citation
“…This comes both as a direct result of the high temperatures reached during a forest fire, but also indirectly through changes to soil chemical and physical properties, like a pH increase, enhanced hydrophobicity or changes of available nutrients (Certini, 2005).…”
Section: Introductionmentioning
confidence: 99%